Characterizing the transcriptional adaptation of Staphylococcus aureus to stationary phase growth. Issue 5 (8th May 2016) - Weiss, Andy; Broach, William H.; Shaw, Lindsey N.
Abstract : Staphylococcus aureus is an important human pathogen that causes life-threatening infections, and is resistant to the majority of our antibiotic arsenal. This resistance is complicated by the observation that most antibacterial agents target actively growing cells, thus, proving ineffective against slow growing populations, such as cells within a biofilm or in stationary phase. Recently, our group generated updated genome annotation files for S. aureus that not only include protein-coding genes but also regulatory and small RNAs. As such, these annotation files were used to perform a transcriptomic analysis in order to understand the metabolic and physiological changes that occur during transition from active growth to stationary phase; with a focus on sRNAs. We observed ∼24% of protein-coding and 34% of sRNA genes displaying changes in expression by ≥3-fold. Collectively, this study adds to our understanding of S. aureus adaptation to nutrient-limiting conditions, and sheds new light onto the contribution of sRNAs to this process. Abstract : The authors investigated the adaptation of the Staphylococcus aureus transcriptome to stationary phase growth by quantifying the expression of recently annotated small RNA as well as protein-coding genes.